Advanced DNA Detection via Multispectral Plasmonic Metasurfaces - Di Meo, Valentina; Moccia, Massimo; Sanità, Gennaro; Crescitelli, Alessio; Lamberti, Annalisa; Galdi, Vincenzo; Rendina, Ivo; Esposito, Emanuela (Frontiers in Bioengineering and Biotechnology, 2021)
We propose and demonstrate a sensing platform based on plasmonic metasurfaces for the detection of very low concentrations of deoxyribo-nucleic acid (DNA) fragments. The platform relies on surface-enhanced infrared absorption spectroscopy, implemented via a spatial multiplexing of the metasurface, with different regions (“pixels”) engineered so as to separately cover the medium-infrared range extending from the functional-groups to the fingerprint region. With a suitable bio-functionalization, this enables univocal and label-free recognition of specific molecules. For experimental validation, we fabricate a large-area gold metasurface on a silicon chip, and functionalize it with a recognition layer of peptide nucleic acid (PNA). Our experimental results indicate the possibility to detect complementary DNA fragments in concentrations as low as 50 fM, i.e., well below the value attained by standard methods, with additional advantages in terms of processing time, versatility and ease of implementation/operation